Pedigree-based QTL analysis of flower size traits in two multi-parental diploid rose populations - Rawandoozi, Zena; Young, Ellen L.; Liang, Shuyin; Wu, Xuan; Fu, Qiuyi; Hochhaus, Tessa; Yan, Muqing; Rawandoozi, Maad Y.; Klein, Patricia E.; Byrne, David H.; Riera-Lizarazu, Oscar (Frontiers in Plant Science, 2023)
Rose (Rosa spp.) is one of the most economically important ornamental species worldwide. Flower diameter, flower weight, and the number of petals and petaloids are key flower-size parameters and attractive targets for DNA-informed breeding. Pedigree-based analysis (PBA) using FlexQTL software was conducted using two sets of multi-parental diploid rose populations. Phenotypic data for flower diameter (Diam), flower weight (fresh (FWT)/dry (DWT)), number of petals (NP), and number of petaloids (PD) were collected over six environments (seasons) at two locations in Texas. The objectives of this study were to 1) identify new and/or validate previously reported QTL(s); 2) identify SNP haplotypes associated with QTL alleles (Q-/q-) of a trait and their sources; and 3) determine QTL genotypes for important rose breeding parents. Several new and previously reported QTLs for NP and Diam traits were identified. Also, QTLs associated with flower weight and PD were identified for the first time. Two major QTLs with large effects were mapped for all traits. The first QTL was at the distal end of LG1 (60.44 to 60.95 Mbp) and was associated with Diam and DWT in the TX2WOB populations. The second QTL was consistently mapped in the middle region on LG3 (30.15 to 39.34 Mbp) and associated with NP, PD, and flower weight across two multi-parent populations (TX2WOB and TX2WSE). Haplotype results revealed a series of QTL alleles with differing effects at important loci for most traits. This work is distinct from previous studies by conducting co-factor analysis to account for the DOUBLE FLOWER locus while mapping QTL for NP. Sources of high-value (Q) alleles were identified; ‘Old Blush’, and Rosa wichuraiana from J14-3 for Diam, while ‘Violette’ and PP-J14-3 were sources for other traits. Also, the source of the low-value (q) alleles for Diam was ‘Little Chief’, and Rosa wichuraiana through J14-3 was for the remaining traits. Hence, our results can potentially inform parental/seedling selections as means to improve ornamental quality in roses and a step towards implementing DNA-informed techniques for routine use in rose breeding programs.